Developing Organizational Guidelines for the Prevention and Management of Suicide in Clients and Carers Receiving Palliative Care in Australia. (April 2016) - O'Connor, Margaret; Groom, Jane; Watson, Michelle; Harris, Pamela
This article describes the process of developing a suicide guideline in palliative care. Little literature was available, but utilizing the partnership model, a working party consulted with each discipline regarding specific requirements. The working party experienced significant challenges in creating policy that would adequately cover the diverse needs of all members of the palliative care team, as it was recognized that all staff needed guidance. The final guideline incorporated specific action plans for each discipline; mandatory training for all staff was endorsed through a recognized suicide alertness training program; advanced training in suicide intervention skills for key clinical staff will be required; and a "Rapid Plan Team" was recommended. This policy development has required significant work and the combined expertise of many disciplines.